Implementation of Guided Inquiry as an Effort to Improve Critical Thinking Ability of Students - Wijayanti, Murwani Dewi; Rahardjo, Sentot Budi; Saputro, Sulistyo; Mulyani, Sri (Sebelas Maret University, 2016)
Nowadays, there are many efforts to improve the quality of human resources through education, such as by applying a wide variety of learning models. An appropriate model of can enhance the students critical thinking ability. Critical thinking can appear anytime in the process of judgment, decision, or problem solving in general. Whenever, someone tries to figure out what have to believe and what you need to know the reason. Through business process and reflective processing such as reading, writing, speaking and listening, it can be done critically. Various attempts were made by the teachers in an effort to improve the studentsâ critical thinking ability. One model of learning is guided inquiry. This paper talks about definition and implementation of guided inquiry as an effort to improve studentsâ thinking ability through research literature. The nature of the research is descriptive analysis. This paper uses philosophical and pedagogical approach. Meanwhile, the data collection uses documentation. Analisis data used in this research is content analysis (content analysis). From the analysis we may conclude that adoption of guided inquiry can be used by educators to enhance the studentsâ critical thinking ability.Â